Pengaruh Tax Avoidance, Tax Risk, Transfer Pricing, Leverage dan Profitabilitas terhadap Corporate Risk pada Perusahaan Sektor Energi dan Basic Materials - Angel, Viorentina; Suhartono, Sugi (Jurnal Akuntansi, 2026)
This research aims to examine the effect of tax avoidance, tax risk, transfer pricing, leverage, and profitability on corporate risk. The research is grounded in Agency Theory and Signaling Theory. Previous studies have shown different results regarding corporate risk. Moreover, studies that combine tax and financial factors to explain corporate risk, especially in Energy and Basic Materials companies in Indonesia, are still limited. The research object consists of companies in the Energy and Basic Materials sectors listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The sampling technique used was purposive sampling, consisting of 41 companies and resulting in 123 samples. Secondary data were obtained from IDX financial statements and stock price data from finance.yahoo.com. The analysis included descriptive analysis test, pooling test, normality test, autocorrelation test, multicollinearity test, heteroscedasticity test, F-test, t-test, and coefficient of determination test (R²), processed using IBM SPSS version 31. The research findings indicate that there is sufficient evidence that tax avoidance, tax risk, transfer pricing, and leverage have a positive and significant effect on corporate risk. Meanwhile, there is insufficient evidence that profitability has a negative effect on corporate risk.